Readings through the texts of Rigoberta Menchú and Dayamani Barla a comparative study - Saurabh, Saket Suman (Estudios e investigaciones, 2017)
The present project proposes to look at two "texts" from India and Latin America; Dayamani Barla and Rigoberta Menchú. I use the word "texts" as a generic term referring to all their activism through life experiences, struggles and their writings. I submit that each of these element complement each other to comprise what I state as a "text". Rigoberta is from Guatemala and belongs to Maya Quiche community, and had suffered a lot along with her community members at the hands of "Ladinos" (The landlords of white skin "from native Indians and Spanish colonizers," who exploited local native people in their cotton, sugarcane and coffee farms in the high lands) because they were being exploited in terms of low wages and the worst working conditions.